Design of Photovoltaic-Wind-Diesel-Battery Hybrid Energy System: Perspective of Energy Management System for Stand Alone Power Solution - Adefarati, T.; Bawonda, F. I.; Olulope, P. K.; Onipe, J. A.; Adisa, K. O.; Idris, H. D.; Abubakar, A. O.; Alabi, G. S.; Borisade, G. S.; Sobowale, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Design of Photovoltaic-Wind-Diesel-Battery Hybrid Energy System: Perspective of Energy Management System for Stand Alone Power Solution